2020
DOI: 10.1038/s41598-020-73083-3
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary and ontogenetic changes of the anatomical organization and modularity in the skull of archosaurs

Abstract: Comparative anatomy studies of the skull of archosaurs provide insights on the mechanisms of evolution for the morphologically and functionally diverse species of crocodiles and birds. One of the key attributes of skull evolution is the anatomical changes associated with the physical arrangement of cranial bones. Here, we compare the changes in anatomical organization and modularity of the skull of extinct and extant archosaurs using an Anatomical Network Analysis approach. We show that the number of bones, th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 89 publications
(157 reference statements)
0
11
0
Order By: Relevance
“…Early diapsids are thought to have been adapted to feeding on agile prey (Evans, 2008), for which an increased intracranial mobility was necessary (see discussion further below). More crownward diapsids (Lee et al, 2020;Plateau and Foth, 2020) differ from the modeled early diapsids. Differences are likely associated with a change to a more carnivorous feeding behavior as exemplified in archosauriform evolution with †Euparkeria capensis representing a transitional form (Sookias et al, 2020) or †Tyrannosaurus rex showing specific snout adaptations .…”
Section: From Robust To Agile-and Back To Robust Prey: Diapsid Evolutionmentioning
confidence: 83%
See 2 more Smart Citations
“…Early diapsids are thought to have been adapted to feeding on agile prey (Evans, 2008), for which an increased intracranial mobility was necessary (see discussion further below). More crownward diapsids (Lee et al, 2020;Plateau and Foth, 2020) differ from the modeled early diapsids. Differences are likely associated with a change to a more carnivorous feeding behavior as exemplified in archosauriform evolution with †Euparkeria capensis representing a transitional form (Sookias et al, 2020) or †Tyrannosaurus rex showing specific snout adaptations .…”
Section: From Robust To Agile-and Back To Robust Prey: Diapsid Evolutionmentioning
confidence: 83%
“…Functional considerations of skull anatomy cannot be performed without proper knowledge on muscle anatomy, which is usually barely described in the literature for extant taxa and usually misses relevant information of muscle fiber-compositions and orientations and tendinous components. For extinct taxa, only gross morphology of musculature can be reconstructed on a rough anatomical level, mainly based on phylogenetic bracketing and by considering indications of possible attachment sites on bones (Witzmann and Werneburg, 2017) Rasskin-Gutman and Esteve-Altava, 2014; Diogo et al, 2015;Molnar et al, 2017;Lee et al, 2020;Plateau and Foth, 2020;Sookias et al, 2020). Rasskin-Gutman (2003) provided a first attempt to study skull modularity in relation to temporal openings and found, by comparing nine different tetrapod skulls, that the orbit is surrounded by a rather simple modular arrangement with one element attaching to at least three other adjacent elements.…”
Section: Significance Of the Anatomical Network Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Within‐module integration levels have also been linked to the generation of disparity: lower integration within modules is linked to higher magnitudes of cranial disparity in mammals (Goswami and Polly 2010a) and archosaurs (Felice et al 2018; Lee et al. 2020). Thus, the architecture of trait interactions may affect an organism's response to selection, directing lineage diversification along favored pathways (Shirai and Marroig 2010; Melo et al.…”
Section: Figurementioning
confidence: 99%
“…Within the same organism, different traits can experience different types of heterochronies-a phenomenon known as mosaic or modular heterochrony (Bastir & Rosas, 2009;Koyabu et al, 2014). In birds, enlargement of the eyes and brain and shortening of the face are considered paedomorphic, while enlargement of the premaxilla to form a beak and the fusion of cranial bones within the same skull are peramorphic (Bhullar et al, 2012;Lee et al, 2020). In humans, the base of the skull that enables upright walking and the larger brain, cranium, and body sizes, result from an extended growth period and are peramorphic compared to ancestral apes (hypermorphosis).…”
mentioning
confidence: 99%